2005
DOI: 10.1359/jbmr.041221
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Thoracic Vertebral Bone Attenuation With Calcium-Based Phosphate Binders in Hemodialysis

Abstract: The average serum phosphorus and calcium x phosphorus products were similar for both groups, although the average serum calcium concentration was significantly higher in the calcium-treated group. Compared with sevelamer-treated subjects, calcium-treated subjects showed a decrease in thoracic vertebral trabecular bone attenuation (p = 0.01) and a trend toward decreased cortical bone attenuation. More than 30% of calcium-treated subjects experienced a 10% or more decrease in trabecular and cortical bone attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 46 publications
5
68
1
5
Order By: Relevance
“…In the study presented here, VBD was assessed by CT, a method that allows distinction between cortical and trabecular bone and avoids miscalculation of the VBD due to the presence of aortic calcification. In dialysis patients, the few studies using CT have found an association between low trabecular VBD and the extent of CAC (8,9). Herein, we demonstrated that such association starts early in the course of CKD.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the study presented here, VBD was assessed by CT, a method that allows distinction between cortical and trabecular bone and avoids miscalculation of the VBD due to the presence of aortic calcification. In dialysis patients, the few studies using CT have found an association between low trabecular VBD and the extent of CAC (8,9). Herein, we demonstrated that such association starts early in the course of CKD.…”
Section: Discussionsupporting
confidence: 50%
“…More importantly, loss of BMD has been implicated with the progression of CAC over time (6,7). In dialysis patients, the few studies using computed tomography (CT) have found an association of vertebral bone density (VBD) with the extent of CAC (8,9). CAC is a highly prevalent condition among CKD patients, and it has been described as a strong predictor of worse outcome in the dialysis population (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data, however, suggest that these goals often are not met (29,40) with conventional hemodialysis. Newer vitamin D analogues (41), calcimimetics (42), and noncalcium-based phosphate binders (43)(44)(45) all are welcome developments in the effort to improve metabolic control; however, failure to achieve mineral metabolism goals remains a significant problem (46). A consensus on how best to improve achievement of K/DOQI goals for mineral metabolism has not yet been reached in the context of conventional hemodialysis.…”
Section: Mineral Metabolism: How To Get Control?mentioning
confidence: 99%
“…Studies have shown that sevelamer attenuates progression of vascular calcification and prevents reduction in thoracic vertebral bone mineral density. 7,9,10 Bone biopsy is the recognized gold standard for the diagnosis and evaluation of renal bone disease. [11][12][13] Previous reports assessing changes in vertebral bone with phosphate binders by electron-beam tomography (EBT) did not assess changes in bone histology.…”
mentioning
confidence: 99%
“…[11][12][13] Previous reports assessing changes in vertebral bone with phosphate binders by electron-beam tomography (EBT) did not assess changes in bone histology. 9,10 Thus, a study using bone biopsies was conducted to compare the effects of sevelamer hydrochloride and calcium carbonate on bone histology. Figure 1.…”
mentioning
confidence: 99%